STUDENTS’ PERCEPTION OF USING “DICTIONARY POCKET” AS A MEDIUM TO IMPROVE THEIR VOCABULARY MASTERY - Titi Mariah; Yanti Yusanti; Ula Nisa El Fauziah (IKIP Siliwangi, 2019)
Vocabulary known as an essential skill for learning to read, speak, write and listen. It is important to find the appropriate technique in order to improve students’ vocabulary mastery. The researchers did research with focuses on students’ perception towards using “dictionary pocket” in order to improve their vocabulary mastery. It was conducted using a qualitative descriptive method. To collect the data, the researchers use the instruments of an open-ended questionnaire and interview section. The samples were 36 students of second grade from Broadcasting major at SMK Negeri 1 Cimahi. The result of the questionnaire shows that it was found that almost all of the students feel that with learn vocabulary can be easier when they use the technique of remembering dictionary pocket. They also agree that dictionary pocket is an appropriate technique which is used to learn vocabulary. In the other hand, the result of interview shows, the students concede that they are feel helped and being motivated. It can be sum up that dictionary pocket is suitable to strengthen their vocabulary mastery. Dictionary pocket is useful enough because it can help them when they forget the word.